Coalgebraic methods in computer science : 13th IFIP WG 1.3 International Workshop, CMCS 2016, colocated with ETAPS 2016, Eindhoven, The Netherlands, April 2-3, 2016, Revised selected papers /: 13th IFIP WG 1.3 International Workshop, CMCS 2016, colocated with ETAPS 2016, Eindhoven, The Netherlands, April 2-3, 2016, Revised selected papers. (2016) - Unknown
No abstract available